2007
DOI: 10.1002/pds.1470
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pioglitazone and rosiglitazone for hospitalization for acute myocardial infarction in type 2 diabetes

Abstract: This retrospective cohort study showed that pioglitazone, in comparison with rosiglitazone, is associated with a 22% relative risk reduction of hospitalization for AMI in patients with type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(12 citation statements)
references
References 22 publications
2
9
1
Order By: Relevance
“…Our results are consistent with a previously suggested protective effect for metformin (18), more neutral effect for pioglitazone (16,17), and potential relative adverse cardiovascular safety profile for rosiglitazone (19,3,4,20). In particular, our results comparing rosiglitazone with pioglitazone complement other recent findings (19,20) and are not likely to be confounded by indication, given the similar prescribing patterns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are consistent with a previously suggested protective effect for metformin (18), more neutral effect for pioglitazone (16,17), and potential relative adverse cardiovascular safety profile for rosiglitazone (19,3,4,20). In particular, our results comparing rosiglitazone with pioglitazone complement other recent findings (19,20) and are not likely to be confounded by indication, given the similar prescribing patterns.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, our results comparing rosiglitazone with pioglitazone complement other recent findings (19,20) and are not likely to be confounded by indication, given the similar prescribing patterns. Together, these findings demonstrate that methods for medical record surveillance may provide useful adjunct methods to assess postmarketing drug safety.…”
Section: Discussionsupporting
confidence: 86%
“…A retrospective cohort study, which investigated the risk of AMI during 2003–2006, found that the crude incidence rates of MI were 933 for pioglitazone and 1,113 per 100,000 person-years for rosiglitazone patients [6]. The current study’s rate of MI, covering 2003–2010, was 454 per 100,000 person-years (Table 3), in agreement with a recognized—but not well understood—trend of a decline in CV events in recent years [33, 34].…”
Section: Discussionmentioning
confidence: 99%
“…Both TZDs improve insulin sensitivity through their action at PPAR gamma receptors—with similar effects on glucose levels—but pioglitazone demonstrates a different effect on lipid metabolism [4, 5] and further has been associated with a reduction in the risk of hospitalization for acute myocardial infarction (AMI) compared with rosiglitazone [6]. Results from the PROactive (PROspective pioglitAzone Clinical Trial In macroVascular Events) study have shown that pioglitazone, in conjunction with standard treatments for diabetes and cardiovascular (CV) conditions, can reduce the risk of the composite endpoint of all-cause mortality, non-fatal myocardial infarction (MI) and stroke [7].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found a significant difference in the risk of MI and coronary revascularization between sulfonylureas (higher risk) and metformin (lower) risk, but no significant difference when either agent was compared with rosiglitazone, which appeared to impart a level of risk somewhere between the two [76]. A retrospective cohort study comparing rosiglitazone and pioglitazone appears to support the results of the meta-analyses [77]. The risk of hospitalization for MI was significantly lower for pioglitazone compared with rosiglitazone (HR=0.78, 95% CI [0.63, 0.96]), as was the risk of the composite of MI and coronary revascularization (HR=0.85, 95% CI [0.75, 0.98]).…”
Section: What Are the Observed Effects Of Tzds On Actual Clinical Outmentioning
confidence: 89%